2018
DOI: 10.18632/oncotarget.24481
|View full text |Cite
|
Sign up to set email alerts
|

Bcl-xLas a poor prognostic biomarker and predictor of response to adjuvant chemotherapy specifically inBRAF-mutant stage II and III colon cancer

Abstract: PurposeBRAF mutation occurs in 8–15% of colon cancers (CC), and is associated with poor prognosis in metastatic disease. Compared to wild-type BRAF (BRAFWT) disease, stage II/III CC patients with BRAF mutant (BRAFMT) tumors have shorter overall survival after relapse; however, time-to-relapse is not significantly different. The aim of this investigation was to identify, and validate, novel predictors of relapse of stage II/III BRAFMT CC.Experimental designWe used gene expression data from a cohort of 460 patie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…The combination of the BTSA1.2 and Navitoclax demonstrated synergistic therapeutic efficacy in colorectal tumors while being remarkably tolerated in vivo, indicating that this therapeutic strategy may be highly promising for solid tumors. Previous evidence has shown that high expression levels of BCL-XL plays a key role in colorectal tumors formation and therapy resistance [47][48][49][50] . Despite such evidence, the application of Navitoclax in colorectal tumors including our work here suggests that BCL-XL inhibition is not efficient as single agent treatment and is not able to promote apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The combination of the BTSA1.2 and Navitoclax demonstrated synergistic therapeutic efficacy in colorectal tumors while being remarkably tolerated in vivo, indicating that this therapeutic strategy may be highly promising for solid tumors. Previous evidence has shown that high expression levels of BCL-XL plays a key role in colorectal tumors formation and therapy resistance [47][48][49][50] . Despite such evidence, the application of Navitoclax in colorectal tumors including our work here suggests that BCL-XL inhibition is not efficient as single agent treatment and is not able to promote apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…BTSA1.2 and Navitoclax combination is efficacious in resistant colorectal xenografts. BCL-XL plays a key role in colorectal tumors formation and therapy resistance [47][48][49][50] . However, there is no clinical testing of BH3-mimetics for colorectal tumors as preclinical studies suggest that only BCL-XL inhibition is not sufficient to effectively induce apoptosis [47][48][49][50] .…”
Section: Combination Of Btsa12 and Navitoclax Is Well Tolerated In Vivomentioning
confidence: 99%
See 1 more Smart Citation
“…Despite careful curation of the NCDB of most cancer patients in the US, various variables such as specific chemotherapy or systemic agent utilized, disease free survival, recurrence rates, objective assessment of response to treatment and prior history of malignancies ( 33 ). Further, missing molecular characteristics such as BRAF mutation have been established as major determinants of therapy response and survival in colorectal cancer ( 34 ). Neoadjuvant or preoperative therapy is typically used in rectal cancers with clinical stage T3N0 and greater.…”
Section: Discussionmentioning
confidence: 99%
“…where 212 patients had died from a CRC-specific cause. Subsets of Colo-661 have been used in previous publications and the data had therefore undergone prior manual QC operations [19,20,[48][49][50][51][52][53][54]. Researcherdefined data modalities span clinical pathology, epidemiology, mutation, and treatment and outcomes.…”
Section: Datasetmentioning
confidence: 99%